2009
DOI: 10.1108/00907320911007001
|View full text |Cite
|
Sign up to set email alerts
|

Blogging toward information literacy: engaging students and facilitating peer learning

Abstract: Purpose This paper describes how a course-integrated blog was used to facilitate the learning of information literacy skills. It also reports on how the effectiveness of the blog was evaluated. Research limitations/implications These results reflect just one course at a single university, therefore it is not possible to use the findings to make generalizations. The study could serve as a starting point for further inquiry into the evaluation of blogs as a support tool. Originality/value While others have repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Validating the findings of recent studies (Chan & Cmor, 2009;Zinger & Sinclair, 2013;Dyer, 2017), this study also found out that blogging can facilitate peer-to-peer engagement through comments and feedback among their blog posts. Because students were required to read and comment on at least five blog posts of their classmates every week, they were aware that they had audience or readers.…”
Section: Because Of This Blog I Learned To Research and Check The Spsupporting
confidence: 78%
“…Validating the findings of recent studies (Chan & Cmor, 2009;Zinger & Sinclair, 2013;Dyer, 2017), this study also found out that blogging can facilitate peer-to-peer engagement through comments and feedback among their blog posts. Because students were required to read and comment on at least five blog posts of their classmates every week, they were aware that they had audience or readers.…”
Section: Because Of This Blog I Learned To Research and Check The Spsupporting
confidence: 78%
“…While the use of Web 2.0 for information literacy instruction is a relatively new area of study, previous research found that these technologies had the potential to help students improve their information literacy competency (Bobish, 2011;Bussert, Brown, & Armstrong, 2008;Chan & Cmor, 2009;Deitering, 2008;Godwin, 2009). Bobish (2011) examined the connection between ACRL IL standards and Web 2.0 as a tool for supporting various learning outcomes listed within the standards that relate to constructivist pedagogy.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research on the use of Web 2.0 for information literacy instruction typically researched one or two specific Web 2.0 tools (Bussert, Brown, & Armstrong, 2008;Chan & Cmor, 2009;Deitering, 2008;Maggio et al, 2009;Zazzau, 2009). Using four very different Web 2.0 technologies allowed for greater insight into how Web 2.0 could be used for information literacy instruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…User statistics are a useful tool (Chan & Cmor, 2009), as blog content is only valuable if it has an audience. The team made use of the StatCounter tool to see which posts are popular, the number of new users, how many users make return visits, the length of time people spend viewing blog content, and the path they take coming into and leaving the site.…”
Section: Evidencementioning
confidence: 99%